2014
DOI: 10.1111/rda.12395
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical Artificial Insemination in Dogs and Cats: Review of the Technique and Practical Aspects

Abstract: Contents The technique of transcervical catheterization for artificial insemination has gained practical importance over the last 3 and 1 decades in bitches and queens, respectively. The vagina of both species has a thickening of the dorsal aspect called dorsal medial fold, which restricts the lumen of the paracervix, making catheterization of the cervix difficult both with manual and endoscopic techniques. Manual catheters have been used initially in the bitch and are now gradually being replaced by rigid end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The advance of canine reproductive biotechnologies over the last decade have improved breeding management and gamete preservation in both domestic and wild canids (Chastant‐Maillard et al., ; Romagnoli & Lopate, ; Tsutsui, Hori, Endo, Hayama, & Kawakami, ). However, despite such technological progress, detailed characteristics of certain aspects of canine reproductive physiology remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The advance of canine reproductive biotechnologies over the last decade have improved breeding management and gamete preservation in both domestic and wild canids (Chastant‐Maillard et al., ; Romagnoli & Lopate, ; Tsutsui, Hori, Endo, Hayama, & Kawakami, ). However, despite such technological progress, detailed characteristics of certain aspects of canine reproductive physiology remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…On the same time with the tomcat, queen was anesthetized by medetomidine 0.20 ml + Propofol 1.0 ml (7,8). The semen filled catheter was inserted into the vagina and 27.5 µL extended semen is deposited.…”
Section: Bir Kedide Suni Tohumlama: Türkiye'de Ilk Defa Doğumla Sonuç...mentioning
confidence: 99%
“…Transcervical artificial insemination (TCI) was reported from Scandinavia in 1989 and 1991 1 (Linde-Forsberg et al)via catheterisationand New Zealand in 1993 2 (Wilson)via endoscopy; cited by Romagnoli et al 3 In 2012, the TCI procedure was reported by Lopate, 4 and it has subsequently become a relatively common procedure in veterinary clinical canine breeding practice. Australian (Mason et al) 5 and New Zealand (Hollinshead et al) 6 reports have illustrated that the fertility of TCI is the same as, or better than, surgical AI in the canine, especially when using frozen-thawed semen.…”
Section: Ear Editormentioning
confidence: 99%